INTERPRETASI PENONTON TERHADAP KONTEN PRANK DENGAN TARGET ORANG TUA DI KANAL YOUTUBE NINO KUYA - Rimadhani Putri Budiana; Joyo Nur Suryanto Gono; Lintang Ratri Rahmiaji (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
Prank content is currently still a trend using controversial ideas marked by pranks targeting parents on Nino Kuya's YouTube channel which is watched and liked by many viewers. This study aims to describe the audience's interpretation of prank content targeting parents on Nino Kuya's YouTube channel. This study uses a constructivist paradigm with reception theory and active audience theory. John Fiske's semiotic analysis method is used to analyze preferred reading and Stuart Hall's reception analysis method is used to determine the interpretive position of the audience of teenagers and parents. The dominant meaning in this content is (1) children may prank their parents, (2) educational and entertaining prank messages, (3) reasonable parental reactions to get angry and forgive children's pranks, (4) parents are allowed to control dominant child, and (5) healthy and normal parent-child relationship. The results of the study show the similarity in meaning that pranks target parents tend to be negotiated. Meanwhile, the diversity of meanings arises when the informant interprets the elements of parental reactions and parental communication patterns where the child informants tend to reject parental dominant control. Meanwhile, parent informants accept the dominant meaning offered. Furthermore, half of the informants tended to be dominant, a few negotiated, and the others rejected the healthy and normal relationship between parents and children in the prank content. Overall, it was found that meaning tended to be in a negotiating position regarding the dominant meaning offered because of the variant informants in the form of children and parents as well as differences in the culture of the informant's family and Nino Kuya's family.